2002
DOI: 10.1103/physrevb.66.224410
|View full text |Cite|
|
Sign up to set email alerts
|

Structure and magnetism of small rhodium clusters

Abstract: We report a systematic study of the structural and magnetic properties of free-standing rhodium clusters (Rh N , 4рNр26). The geometrical structures of the global minima and lowest energy isomers were obtained with a semiempirical Gupta potential and employing a global evolutive search algorithm. The spin-polarized electronic structure and related magnetic properties of these geometries were calculated by solving selfconsistently a spd tight-binding Hamiltonian. We determined the possible coexistence of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 54 publications
5
32
0
Order By: Relevance
“…Unlike the results of Rh 2 , the rhodium trimer has two nearly degenerate states: a quartet equilateral triangle (D 3h ) 4 A 00 1 state and a sextet isosceles triangle (C 2v ) 6 A 2 state. This result agrees well with other calculations [14,43,44]. However, the newest studies on structure Rh n (n = 2-9) carried out by Beltrán and coworkers [11] indicated the isosceles triangle (C 2v , 6 A 2 ) is the global minimum of Rh 3 .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Unlike the results of Rh 2 , the rhodium trimer has two nearly degenerate states: a quartet equilateral triangle (D 3h ) 4 A 00 1 state and a sextet isosceles triangle (C 2v ) 6 A 2 state. This result agrees well with other calculations [14,43,44]. However, the newest studies on structure Rh n (n = 2-9) carried out by Beltrán and coworkers [11] indicated the isosceles triangle (C 2v , 6 A 2 ) is the global minimum of Rh 3 .…”
Section: Resultssupporting
confidence: 92%
“…The higher symmetry D 5h of the Rh-5-B found in the quartet state is less stable than the ground state by 8.6 kcal/mol. These structures are in line with the recent calculations by Bae et al [15] and Anguilera-Granja et al [43]. Concerning Rh 5 , our DFT results also predict that it has two degenerate low-energy states, namely the nonet and septet states of Rh-5-A in favor of the high spin state.…”
Section: Rh-5-supporting
confidence: 92%
See 1 more Smart Citation
“…11 In order to improve the atomistic understanding of those problems, a wide range of experimental and theoretical studies have been reported for rhodium clusters in the neutral, cationic, and anionic states. Most of the studies have addressed the atomic structure of Rh n as a function of size, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] the vibrational spectra, 24,25,28 magnetic moments, 3,10,12,14,16,18,22 polarizabilities, 16,29 and the catalytic activity for small molecules. 21,[30][31][32][33][34] Among those studies, hybrid-DFT calculations combined with experimental far-infrared multiple photon dissociation 24,25 have reported that Rh + n clusters have compact structures based on octahedron motifs for n = 6-12 (i.e., only compact structures can explain the vibrational spectra).…”
Section: Introductionmentioning
confidence: 99%
“…(iv) Atomic structures reported in the literature. 3,[12][13][14][15][16]18,[23][24][25][26]47 (v) A large number of different magnetic configurations were calculated for every atomic structure.…”
mentioning
confidence: 99%